PENGAWASAN PERLINDUNGAN ANAK KORBAN KEKERASAN PADA MASA PANDEMI COVID-19 DI KOTA PEKANBARU - Endang Wulandari; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
During the pandemic, the number of victims of violence against children is still high. And if this continues, of course it will damage the future of Indonesia. The Indonesian people are actually aware that children are the next generation of the nation and also as the regeneration of society. It is very sad to see parents not providing protection to their children. Children are beaten, abandoned, and so on. Are parents not aware that it violates human rights? This paper aims to conduct an in-depth assessment and critique of the factors that cause violence against children and to analyze the forms of protection provided to children as victims of violence in the city of Pekanbaru. This research is a study that uses a qualitative methodology. This research is descriptive, describing the reality correctly regarding the protection of child victims of violence in the city of Pekanbaru. Qualitative research aims to reveal certain social situations by describing the true reality. The results of this study are the protection of child victims of violence carried out by the Office of Women's Empowerment and Child Protection in Pekanbaru City has not been maximized. This is caused by several factors, namely the lack of environmental awareness and limited human resources. Keywords: Protection, Supervision